SOME VARIABLES THAT RELATED WITH ATTITUDES OF RURAL YOUNG’S TOWARDS AGRICULTURAL WORK IN TALKEF DISTRICT / NENAVA GOVERNORATE - Ahmad A. Talip Ali Al talip (Mesopotamia Journal of Agriculture)
This research aims at identifying the attitudes of rural youth towards agricultural work in talkef District and relationship with some variables. Questionnaire used in data collection consist of two parts first one included personal social, economical, communicational.asecond part consisted of (26) items to measure attitudes of rural young’s towards agricultural work. The data collected from 80 farmers which represent 5% of population. After testing the validity of the questionnaire, reliability was measured by using split-half method. The data were collected by personal interview and analyzed by using(:Person’s correlation) The results revealed that (71.25%)of respondent were of negative attitudes towards the agriculture work, (26.25%) were of nutral and (2.50%) of respondents were of positive attitudes. Also the results showed that there were positive relationship between attitudes of rural youth towards the agriculture work and variables(age, members of family involved in agricultural work, agricultural cultivated area, cosmopolitans). But there were no relationship between attitudes of rural youth owards the agriculture work and variables, level of education, type of carrier type of farm ownership,).